If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + 5c = 0 Combine like terms: 7c + 5c = 12c 12c = 0 Solving 12c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '12'. c = 0 Simplifying c = 0
| 1.5x-5=4x | | 2(2x-5)-3+2=x+9 | | b^3-4b^2=21b | | -16=(-x) | | 9f+2f= | | 7v+4v= | | -38-(-14)= | | ln(8-x)=ln(3x-2)+ln(x+2) | | -6z+8=-13 | | y=.66x-1.25 | | 1.5y-12=60 | | ln(8-x)=ln(3x-2)+ln(x-2) | | 8(3x-19)=15x+7 | | .5(4x+1)(3x)=27 | | -m+2n=3 | | 4-10.00+4=44 | | 0.04c=5 | | 3-2y=-8 | | 5r^2-44r+120=-50+11r | | -x+7=-13 | | 16-a=-14 | | 11=15t+5t^2 | | x+ay=byequals | | 2x^5-162=0 | | 8h^2-18hj-5j^2= | | 1.5y-12*4=180 | | (11+5v)-(13v+2)= | | 8-1x+4x=2-3x | | 17+2(2n-12)=1 | | -6m+4=2 | | -2+3(-1)=-(-1+6) | | -10y+18=-(5y-7)+6y |